2007
DOI: 10.1177/1534734607305597
|View full text |Cite
|
Sign up to set email alerts
|

A Retained Sponge Is a Complication of Vacuum-Assisted Closure Therapy™

Abstract: Vacuum-assisted closure (VAC) system has become a widely used, efficacious, and overall safe method for managing many types of open wounds. The authors present a case of a rare but avoidable complication caused by a retained piece of sponge after VAC therapy (KCI Inc, San Antonio, TX). They emphasize the need for awareness and careful evaluation of the patient who receives VAC therapy to avoid diagnostic confusion and morbidity to the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…Other complications reported are few. There is one report about a retained piece of sponge [17], and reports about ventricle ruptures caused by direct contact of the sharp edges of the loosen sternum with tissues underneath as in our case [15]. …”
Section: Commentsmentioning
confidence: 87%
“…Other complications reported are few. There is one report about a retained piece of sponge [17], and reports about ventricle ruptures caused by direct contact of the sharp edges of the loosen sternum with tissues underneath as in our case [15]. …”
Section: Commentsmentioning
confidence: 87%
“…After fasciotomy, the wound is usually managed open and dressed sterilely with moist dressings to protect the tissue from drying and retraction [2,5]. Alternatively, negative pressure wound therapy (NPWT) can be employed [2,5,7,9,[13][14][15][16][17][18][19][20], or numerous techniques can be performed for staged wound closure aiming for gradual approximation of skin edges once the edema begins to resolve ( Two pins are threaded through the dermis of the wound margins, and two U-shaped hooked arms engage the pins through the overlying skin surface. A threaded screw passes through the centers of the arms, and when the screw is turned by a tension knob at its free end, the distal arm, which is loose, rides over the screw and is pulled over, facilitating reapproximation (continued) 9 Fasciotomy Wound Management…”
Section: Delayed Primary Wound Closurementioning
confidence: 99%
“…Retained VAC sponges have rarely been reported in literature. In our brief review, we have identified five earlier cases (3)(4)(5)(6)(7)(8). However, we would like to underline that the lack of reporting in literature does not necessarily reflect Letter to the Editor A. Rencuzogullari the rarity of incidents.…”
Section: Discussionmentioning
confidence: 98%